Tradisi Petik Laut Sebagai Simbol Identitas Masyarakat di Kecamatan Puger - Ananda Ines Putri Winanti; Nur Intan Mutiara; Esha Ayu Triana Waskita Putri (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Petik laut is a tradition in the Puger sub-district. This tradition is carried out as a form of request that the lives of the Puger people be kept away from danger. Public belief that arises from mystical events that occur to fishermen at sea is a hidden behavior carried out by the community. This behavior ultimately forms a thought pattern that society expresses in the form of real actions called external behavior. Just like what the puger community does to avoid harm, they carry out the petik laut tradition as a symbol of wishing. Even today, this tradition is still being preserved and has become the identity of the Puger people. This research uses the perspective of symbolic interactionism theory proposed by George Hearbert Mead. According to Mead, identity emerges and develops through activities and between social relationships. The aim of this research is to find out whether the petik laut tradition as a symbol of community trust can be used as an identity for the community itself. The type of research is qualitative research with an ethnographic approach. The results of the research show that the petik laut tradition as a symbol of the puger community's belief in magical things in the sea has been able to become an identity for the Puger community.